Evaluation of Learning Implementation Islamic Religious Education - Yuni Masrifatin; Eliana Masfufah; Makherus Sholeh; Muhamad Fatih Rusydi Syadzili; Muhammad Arif Syihabuddin (IERA, Islamic Education and Research Academy, 2024)
This study evaluates the implementation of Islamic Religious Education (PAI) at SMPN 1 Ngronggot Nganjuk. The role of Islamic education teachers is crucial, as they are responsible for not only teaching but also evaluating students' understanding and application of Islamic principles. The research uses a qualitative method, employing interviews, observations, and document analysis to gather data from the Islamic education teachers at the school. The findings reveal that the implementation of PAI at SMPN 1 Ngronggot has been carried out effectively, with significant efforts made to engage students and ensure they grasp the religious teachings. The study highlights the importance of continuous evaluation to enhance the effectiveness of Islamic education and prevent issues such as juvenile delinquency.